Molecular Profiling of Beer Wort Fermentation Diversity Across Natural Saccharomyces Eubayanus Isolates - Cubillos-Riffo, F; Mardones-Opazo, W; Oporto-Donoso, C; Villarroel-Figueroa, C; Urbina, K (John Wiley and Sons Ltd, 2020)
The utilization of S. eubayanus has recently become a topic of interest due to the novel organoleptic properties imparted to beer. However, the utilization of S. eubayanus in brewing requires the comprehension of the mechanisms that underlie fermentative differences generated from its natural genetic variability. Here, we evaluated fermentation performance and volatile compound production in ten genetically distinct S. eubayanus strains in a brewing fermentative context. The evaluated strains showed a broad phenotypic spectrum, some of them exhibiting a high fermentation capacity and high levels of volatile esters and/or higher alcohols. Subsequently, we obtained molecular profiles by generating ‘end-to-end’ genome assemblies, as well as metabolome and transcriptome profiling of two Patagonian isolates exhibiting significant differences in beer aroma profiles. These strains showed clear differences in concentrations of intracellular metabolites, including amino acids, such as valine, leucine and isoleucine, likely impacting the production of 2-methylpropanol and 3-methylbutanol. These differences in the production of volatile compounds are attributed to gene expression variation, where the most profound differentiation is attributed to genes involved in assimilatory sulfate reduction, which in turn validates phenotypic differences in H2S production. This study lays a solid foundation for future research to improve fermentation performance and select strains for new lager styles based on aroma and metabolic profiles. © 2020 The Authors. Microbial Biotechnology published by John Wiley & Sons Ltd and Society for Applied Microbiology.